Uncovering intelligent self-healing coating : Synthesis strategies, performance, and evaluation techniques – A review - Albarqouni, Yasin M.Y.; Banius, Euodia; Nurul Huda, Abu Bakar; Arman, Abdullah (Russian Association of Corrosion Engineers, 2023)
Extrinsic intelligent-healing corrosion protective coatings have granted significant interest for their sensitivity to environmental stimuli to prevent damage by releasing corrosion inhibitors and polymerizable agents from micro/nanocarriers. Several micro/nanoencapsulation synthesis technologies have been adopted to improve the loading capacity and regulate the releasing behaviour of the healing agents. This context aims to review recent advances in intelligent-healing corrosion protective coatings based on micro/nanocarriers. This review also provides insights for synthesizing strategies and methods of such carriers. The study comprehends further development of extrinsic self-healing coatings by evaluating the advantages and drawbacks of different healing systems. Furthermore, the study includes other corrosion rate evaluation techniques to understand better how to monitor such phenomena.